Awards, honors, and prizes : 1 - Wasserman, Paul.; McLean, Janice W.; Gale Research Company (Detroit : Gale Research Co., 1969)
Listing and description of 2228 awards, honors, and prizes given for outstanding achievement in the United States and Canada. Science, technology, and medicine are among the 28 broad fields covered. Main listing by organization, with address and annotation. Alphabetical index of awards, subject index of awards.
"An international directory of awards and their donors" (varies).
Editors: P. Wasserman and J. McLean <1969->
3rd ed.- issued in two vols.: v. 1, United States and Canada; v. 2, International and foreign awards.
Also issued online.
Latest issue consulted: 8th ed.
SERBIB/SERLOC merged record
Keywords: Awards -- United States -- Directories; Directory